Identification of mega‐environments in Europe and effect of allelic variation at maturity E loci on adaptation of European soybean. (18th February 2017) - Kurasch, Alena K.; Hahn, Volker; Leiser, Willmar L.; Vollmann, Johann; Schori, Arnold; Bétrix, Claude‐Alain; Mayr, Bernhard; Winkler, Johanna; Mechtler, Klemens; Aper, Jonas; Sudaric, Aleksandra; Pejic, Ivan; et al.
Abstract: Soybean cultivation holds great potential for a sustainable agriculture in Europe, but adaptation remains a central issue. In this large mega‐environment (MEV) study, 75 European cultivars from five early maturity groups (MGs 000–II) were evaluated for maturity‐related traits at 22 locations in 10 countries across Europe. Clustering of the locations based on phenotypic similarity revealed six MEVs in latitudinal direction and suggested several more. Analysis of maturity identified several groups of cultivars with phenotypic similarity that are optimally adapted to the different growing regions in Europe. We identified several haplotypes for the allelic variants at the E1, E2, E3 and E4 genes, with each E haplotype comprising cultivars from different MGs. Cultivars with the same E haplotype can exhibit different flowering and maturity characteristics, suggesting that the genetic control of these traits is more complex and that adaptation involves additional genetic pathways, for example temperature requirement. Taken together, our study allowed the first unified assessment of soybean‐growing regions in Europe and illustrates the strong effect of photoperiod on soybean adaptation and MEV classification, as well as the effects of the E maturity loci for soybean adaptation in Europe.